Characterization of a Lipoyl Domain-Independent B-Cell Autoepitope on the Human Branched-Chain Acyltransferase in Primary Biliary Cirrhosis and Overlap Syndrome with Autoimmune Hepatitis - Antal Csepregi; Petra Obermayer-Straub; Susanne Kneip; Anne Kayser; Stephanie Loges; Eleonore Schmidt; Elemér Nemesánszky; Ferenc Szalay; Michael P. Manns; Christian P. Strassburg (Clinical and Developmental Immunology)
Background and aims: Antimitochondrial antibodies (AMA) which recognize pyruvate acetyltransferase (PDC-E2) represent a highly diagnostic feature of primary biliary cirrhosis (PBC). The analysis of immunofluorescence (IF)-AMA-positive sera in PBC patients indicates a conformational epitope located within the lipoyl binding domain of bovine branched-chain acyltransferase (BCKADC-E2) alone or in combination with AMA directed against PDC-E2 the significance of which is presently unclear. In the present study, immunoreactivities and disease associations of AMA against BCKADC-E2 were analyzed. B-cell autoepitopes on BCKADC-E2 were mapped by immunoprecipitation assay.